The impact of the BDNF Val66Met genotype on intrusive memories following trauma exposure and in PTSD is moderated by sex and timing of trauma exposure - Emma Louise Nicholson; Michael Garry; Luke J. Ney; Ken Chia Ming Hsu; Daniel V. Zuj; Kim L. Felmingham (Scientific Reports)
Abstract Intrusive memories are a key symptom of Post-Traumatic Stress Disorder (PTSD). Brain Derived Neurotrophic Factor (BDNF) has been proposed as a possible mechanism influencing intrusive memories in PTSD given its role in synaptic plasticity and memory consolidation. The BDNF Val66Met polymorphism has been linked PTSD susceptibility and episodic memory disturbances however previous research outcomes have been variable, potentially due to a failure to control for important confounds such as sex, ethnicity, BMI, developmental stage and extent of previous trauma experiences. This study explored the relationship between the BDNF Val66Met genotype and emotional memory (intrusive memories and recall) in PTSD controlling for these factors in 276 participants: 53 with PTSD, 118 Trauma Exposed and 105 Controls. Key findings revealed the PTSD group experienced significantly more negative intrusions than Controls, and females more intrusions than males, however there were no group or sex differences in negative memory recall. When developmental stage of trauma was considered in a traumatised sub-sample, BDNF genotype significantly interacted with PTSD status, sex, and developmental trauma stage. This highlights the importance of controlling for sex and timing of trauma on BDNF expression in neurobiological PTSD research, however further research is needed to replicate these preliminary findings and investigate the specific epigenetic and neurobiological mechanisms involved.